Property rights theory and government efficiency: the evidence from India's public sector - Nayar, Baldev Raj
The article gives a comparative account of public and private firms in India's stell and aluminium industries. Compares their financial, perfor,amce and social obligations and comes to the conclusion that superior performance of the private sector lay precisely in the different structure of incentives stemming from private ownership, which geared management to higher efficiency. Thus confirming the theory that by virtue of private ownership alone, the private sector is inherently superior in efficiency to the public sector
Keywords: Stell Authority of India; Property Right; India; Government Enterprise; Government Enterprise - India